Estimated General Equilibrium Models for the Evaluation of Monetary Policy in the US and Europe - Campbell Leith; Jim Malley (Center for Economic Studies and ifo Institute (CESifo), 2002)
A persistent criticism of general equilibrium models of monetary policy which incorporate nominal inertia in the form of the New Keynesian Phillips Curve (NKPC) is that they fail to capture the extent of inflation inertia in the data. In this paper we derive a general equilibrium model based on optimising behaviour, but which also implies a data consistent NKPC. Specifically our model accounts for nominal inertia in both price and wage setting as well for habits in consumption. Using US and European data from 1970 to 1998 our parameter estimates reveal that (i) there is relatively more inertia in price-setting in Europe; (ii) wage contracts last longer in the US; (iii) the extent of backward-looking behaviour in price and wage setting is statistically significant but small in both the US and Europe; and (iv) significant habits effects are present in European consumption. Finally we simulate the effects of monetary policy and find that while the magnitude of the impact of monetary policy on the endogenous variables in our estimated models are similar to other econometric studies, the dynamic paths for variables display less inertia than is typically found in studies which use output gaps to proxy changes in marginal costs.
Keywords: 330